The Territory without a Map: the Sea as a Narratological Frame and Compass in the "Odyssey" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
In this paper, I argue that the sea in Homer’s Odyssey is not the territory suggested by its map, but rather an all-encompassing narratological frame: the sea keeps the isolated locations of Odysseus’ misadventures together. As such the sea in the Odyssey is not just salty, dark-coloured water: it is the continuum in which the narrator’s mind roams, looking for anchor points to which to attach tales and episodes. Searching the virtual space of his imagination, Odysseus presents his series of misadventures and their remote locations as islands in isolation, and uses the sea as an equally virtual space to frame them. For the story-weaving Odysseus, the sea is the fictitious tapestry. And as Teiresias’ warning words show (Od. XI 121-137, repeated in Od. XXIII 265-283), Odysseus somehow has to escape this fiction to find peace, though he cannot escape death coming from it.
Keywords: Odyssey, narratology, Apologue, virtual space, storyworlds